Kajian Yuridis Terhadap Pertanggungjawaban Pidana Pelaku Tindak Pidana Korupsi - Jefta Ramschie; Reimon Supusepa; Yanti Amelia Lewerissa (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The improvement of society's social life, science and technology, has resulted in the growing of criminal acts. Purposes of the Research: The aim of this study is to analyze the criminal liability of the corruption perpetrators and the judges considerations in deciding the case. Methods of the Research: The type of research that used is